High-wear-resistance UV curing metal printing gloss oil and preparation method thereof
By using specific formula ingredients in UV cured iron printing oil to form a solid and smooth surface protective film, the problem of insufficient wear resistance of existing UV cured iron printing oil is solved, and high wear resistance and low cost effects are achieved .
Patent Information
- Application Number
- CN202411656369.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing UV cured iron varnish oil has shortcomings in wear resistance, especially under the requirements of high wear resistance, and its surface protection effect is not as good as that of traditional solvent-based varnish oil.
A highly wear-resistant UV curing iron varnish is used, and its formulation includes free radical curing oligomers, free radical curing monomers, free radical initiators, adhesion accelerators, leveling agents, defoaming agents and wax powders to smoothly The agent, through the combination of these ingredients, forms a solid and smooth surface protective film.
The iron-printing oil has significantly improved surface smoothness and wear resistance without volatile solvents. At the same time, its preparation method is simple, low cost, and has high practical application value.
Smart Images

Figure BDA0005142206400000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of tinplate coatings, and more specifically, to a highly wear-resistant UV-curable tinplate varnish and a preparation method thereof. Background Art
[0002] At present, in the field of tinplate coatings, tinplate is used in large quantities, and a three-layer structure of white tin primer, ink, and varnish is usually adopted. Among them, tinplate varnish is a synthetic resin, usually composed of resin and additives, and the paint film is shiny after curing into a film.
[0003] At present, tinplate varnish is mainly divided into traditional solvent-based varnish (high temperature baking) and new UV curing varnish (ultraviolet lamp curing); among them, the traditional solvent-based product contains 40-60% volatile solvent, which must go through a high temperature baking process of 10-20 minutes, and the solvent evaporates and cross-links to cure to obtain a qualified varnish coating. The production workshop has high temperature and strong odor, and the baked solvent must also be treated in an RTO incinerator, further increasing energy consumption. The high production cost also affects the physical and mental health of workers. In order to balance economic benefits and environmental protection, the transformation of traditional solvent varnish is imperative.
[0004] UV curing varnish has some obvious advantages. First, it uses ultraviolet lamps (mercury lamps / LED lamps) for curing, which has a short curing time and can greatly improve the production efficiency of tinplate varnish. Second, the high solid content in the system reduces environmental pollution and has less impact on human health compared to traditional organic solvents. Currently, UV curing mainly includes free radical curing and cationic curing. Compared with cationic curing, free radical curing is cheap and close to the price of traditional tinplate varnish, and its practical application value is extremely high.
[0005] Although free radical curing varnish has significant advantages in the field of tinplate printing, its wear resistance is poor; wear resistance is crucial for tinplate printing products, especially during the transportation of tinplate can shells, the surface of the varnish is easily rubbed or even penetrated, resulting in product scrapping. Currently, UV curing varnish has some limitations in terms of wear resistance. Under high wear resistance requirements, the protective effect of UV curing varnish on the product surface is not as good as some solvent-based varnishes. Therefore, a new high wear-resistant UV curing tinplate varnish still needs to be developed. Summary of the invention
[0006] In order to prepare a new tinplate varnish which has good lubricity and can form a strong and smooth surface protective film, thereby having high wear resistance, the present application provides a highly wear-resistant UV-curable tinplate varnish and a preparation method thereof.
[0007] In the first aspect, the present application provides a highly wear-resistant UV-curable tinplate varnish, which adopts the following technical solution: A highly wear-resistant UV-curing tinplate varnish comprises the following raw materials in percentage by weight: 40-65% of free radical curing oligomer, 25-44% of free radical curing monomer, 2-4% of free radical initiator, 3-10% of adhesion promoter, 0.05-0.5% of leveling agent, 0.05-0.5% of defoaming agent and 0.5-2% of wax powder lubricant.
[0008] By adopting the above technical scheme, the system does not contain volatile solvents, has low odor, and is good for the environment. The addition of wax powder lubricant and defoaming agent can increase the smoothness and wear resistance of the film surface, so that the printing iron oil has good lubricity and can form a strong and smooth surface protective film, thus having high wear resistance.
[0009] Preferably, the free radical curable oligomer comprises the following raw materials in weight percentage: 20-30% of modified epoxy acrylate resin, 10-20 parts of difunctional polyester acrylate, and 10-15% of silicon-modified polyurethane acrylate.
[0010] By adopting the above technical scheme, modified epoxy acrylic resin, difunctional polyester acrylate and silicon-modified polyurethane acrylate are matched, and the high hardness and high wear resistance of epoxy resin, silicon-based and polyester are utilized to improve the strength and wear resistance of the tinplate varnish after film formation, wherein the silicon-modified polyurethane acrylate can resist the friction of steel wool, effectively resist the wear and scratch of the film layer by the external environment, and protect the surface of the printed matter from damage; and the cross-linking effect of epoxy resin, acrylic acid and polyester further improves the cross-linking structure density between free radical curing oligomers and free radical curing monomers, so that the film layer formed by the tinplate varnish has a higher density, thereby further improving the wear resistance and durability of the film layer; at the same time, epoxy acrylic resin and polyester acrylate can improve the adhesion between the film layer and the substrate surface through cross-linking reaction, so that the varnish can stably adhere to the printed matter and is not easy to be peeled off, thereby further extending the service life of the varnish on the printed matter surface.
[0011] Preferably, the free radical curing monomer comprises the following raw materials in percentage by weight: 20-30% of tripropylene glycol diacrylate, 2-4% of pentaerythritol triacrylate, and 3-10% of cyclotrimethylolpropane formal acrylate.
[0012] By adopting the above technical scheme, tripropylene glycol diacrylate, pentaerythritol triacrylate and cyclotrimethylolpropane formal acrylate are used as crosslinking agents in the ultraviolet curing process. Tripropylene glycol diacrylate contains an allyl double bond. Under ultraviolet irradiation conditions, the epoxy group of epoxy acrylate can be opened and reacted with it to form a new chemical bond, thereby promoting the curing of the resin. In addition, cyclotrimethylolpropane formal acrylate is easy to open the ring and react with the silicon group in the silicon-modified polyurethane acrylate to crosslink, thereby further promoting the curing of the oligomer and improving the wear resistance of the tinplate varnish. At the same time, the hydroxyl group in the free radical curing monomer is easy to react with the carboxyl group in the free radical curing oligomer, thereby further promoting the curing of the film layer, improving the density of the crosslinking structure of the film layer, and cooperating with the filling effect of the silicon base, further improving the wear resistance of the tinplate varnish, extending the adhesion stability of the tinplate varnish on the surface of the printed matter, thereby extending the service life of the tinplate varnish on the surface of the printed matter.
[0013] Preferably, the free radical initiator comprises the following raw materials in weight percentage: 2-Hydroxy-2-methyl-1-phenyl-1-propanone 1-2%, ethyl 2,4,6-trimethylbenzoylphenylphosphonate 1-2%.
[0014] By adopting the above technical solution, 2-hydroxy-2-methyl-1-phenyl-1-propanone and ethyl 2,4,6-trimethylbenzoylphenylphosphonate can efficiently absorb light energy and then convert it into chemical energy, triggering a UV curing reaction and promoting the rapid curing of the tinplate varnish.
[0015] Preferably, the adhesion promoter is a chlorinated polyester resin.
[0016] By adopting the above technical scheme, the chlorine atoms of the chlorinated polyester resin can enhance the polarity of the resin and improve the adhesion of the tinplate varnish; and the high crosslinking density and crystallinity of the chlorinated polyester resin increase the hardness and wear resistance of the tinplate varnish film, and the wax powder lubricant further reduces the friction coefficient, reduces wear, and extends the service life of the tinplate varnish.
[0017] Preferably, the leveling agent is BYK-361N.
[0018] By adopting the above technical solution, BYK-361N, as a leveling agent, can effectively reduce the surface tension of the coating, making it easier to spread evenly on the substrate. In tinplate varnish, it can help form a smoother and flawless coating surface, and also has the advantage of preventing shrinkage holes, avoiding small pits or depressions on the coating surface as much as possible, ensuring the surface quality of the tinplate varnish film layer, and at the same time improving the compatibility between raw materials, further improving the stability of the entire system, thereby ensuring the strength and wear resistance of the tinplate varnish.
[0019] Preferably, the defoaming agent is silicone acrylate.
[0020] By adopting the above technical scheme, the silicon-oxygen bond in the silicone acrylate has a higher bond energy, and is not easy to generate bubbles at high temperatures. Combined with the stability of the silicon-oxygen bond and the flexibility of the silicone acrylate molecular chain, the uniformity of the tinplate varnish film layer is guaranteed during the ultraviolet radiation curing process, and it is not easy to generate bubbles and cause surface pits; combined with silicon-modified polyurethane acrylate, the silicon-based filling effect is further improved, thereby improving the wear resistance of the tinplate varnish.
[0021] Preferably, the wax powder lubricant is PTFE modified polyethylene wax.
[0022] Preferably, the average particle size of the PTFE modified polyethylene wax is 4-6 μm, and the drop melting point is 115-118°C.
[0023] By adopting the above technical solution, polyethylene wax has good lubricity and can form a thin and uniform lubricating film on the surface of the coating, thereby improving the smoothness and touch of the coating. It can also reduce friction, improve the wear resistance of the coating, and extend the service life. Since polyethylene wax forms a thin film on the surface of the coating, it can provide a soft and slippery feel and improve the tactile experience of the product. In addition, due to the low surface tension characteristics of PTFE, its modified polyethylene wax helps to further reduce the friction coefficient of the coating surface. The wax powder with low surface tension can also reduce the adhesion of dust and stains, thereby improving the pollution resistance of the coating.
[0024] In a second aspect, the present application provides a method for preparing a highly wear-resistant UV-curable tinplate varnish, using the following technical solution: A method for preparing a highly wear-resistant UV-curable tinplate varnish comprises the following steps: S1, mixing wax powder lubricant and part of free radical curing monomer, the mass ratio of wax powder lubricant to free radical curing agent monomer is 1:3.5-4.5, stirring, diluting and dispersing, adding to a sand mill and sand milling for 85-95 minutes at a speed of 900-1100r / min to obtain wax slurry; S2, mixing the free radical curing oligomer, the remaining free radical curing monomer, and the adhesion promoter, stirring at 1000-1500 rpm for 25-35 min, mixing evenly, and obtaining a primary mixture; S3, adding a free radical initiator to the initial mixture, mixing and stirring for 25-35 minutes to obtain a composite material; S4. Add wax slurry, leveling agent and defoamer to the composite material, continue mixing and stirring for 25-35 minutes to obtain the finished tinplate varnish.
[0025] By adopting the above technical solution, the tinplate varnish prepared has good lubricity and can also form a strong and smooth surface protective film, thereby having high wear resistance.
[0026] In summary, this application has the following beneficial effects: 1. The tinplate varnish system does not contain volatile solvents, has low odor and is environmentally friendly. The addition of silicon-containing free radical curing oligomers, silicon-containing defoaming agents and PTFE-modified polyethylene wax greatly improves the surface smoothness and wear resistance. In addition, the tinplate varnish is easy to prepare, low in cost, and has high practical application value.
[0027] 2. During the UV curing process, the tinplate varnish can form a uniform protective film, and its surface is enriched with silicon and fluorine groups, which improves the wear resistance of the tinplate products, making them more durable, and avoiding the friction between downstream products such as tanks during long-distance transportation, resulting in surface wear and even bottom exposure. The use of defoamers and PTFE-modified polyethylene wax in varnish helps reduce dust generated during roller coating and tank processing, and improves processing operating conditions. The use of wear-resistant varnish can reduce the uneven distribution of the coating during high-speed printing and improve the stability and consistency of the coating.
[0028] 3. Modified epoxy acrylic resin, difunctional polyester acrylate, and silicon-modified polyurethane acrylate are used together to utilize the high hardness and high wear resistance of epoxy resin, silicon-based and polyester to improve the strength and wear resistance of the tinplate varnish after film formation. Among them, silicon-modified polyurethane acrylate can resist the friction of steel wool, effectively resist the wear and scratch of the film layer by the external environment, and protect the surface of the printed matter from damage; and the cross-linking effect of epoxy resin with acrylic acid and polyester further improves the cross-linking structure density between free radical curing oligomers and free radical curing monomers, so that the film layer formed by the tinplate varnish has a higher density, thereby further improving the wear resistance and durability of the film layer; at the same time, epoxy acrylic resin and polyester acrylate can improve the adhesion between the film layer and the substrate surface through cross-linking reaction, so that the varnish can stably adhere to the printed matter and is not easy to be peeled off, further extending the service life of the varnish on the printed matter surface. DETAILED DESCRIPTION
[0029] The present application is further described in detail below with reference to the embodiments. Example
[0030] The modified epoxy acrylate resin in the following raw materials was purchased from Guangdong Lan Kelu New Materials Co., Ltd., with the brand name L-6102; the difunctional polyester acrylate was purchased from Jiangsu Sanmu Group Co., Ltd., with the brand name 6606; the silicon-modified polyurethane acrylate was purchased from Shenzhen Youyang Technology Co., Ltd., with the brand name T-7515; tripropylene glycol diacrylate, pentaerythritol triacrylate, and cyclotrimethylolpropane formal acrylate were all purchased from Shenzhen Youyang Technology Co., Ltd., with the brand names AM-321, AM-324, and AM-31, respectively. 3; 2-Hydroxy-2-methyl-1-phenyl-1-propanone and ethyl 2,4,6-trimethylbenzoylphenylphosphonate were purchased from IGM Irgacure with brand names 1173 and TPO-L respectively; chlorinated polyester resin was purchased from Allnex Resins Co., Ltd. with brand name EBECRYL418; BYK361 was purchased from BYK Chemical Company of Germany; silicone acrylate was TEGO2700 from Evonik of Germany; PTFE modified polyethylene wax was purchased from Shanghai Yuansheng Hufang New Materials Co., Ltd. with brand name 0674F.
[0031] Example 1: A highly wear-resistant UV-curable tinplate varnish: 40kg of free radical curing oligomer, 39kg of free radical curing monomer, 4kg of free radical initiator, 10kg of adhesion promoter, 0.5kg of leveling agent, 0.5kg of defoaming agent, 1kg of wax powder lubricant; the free radical curing oligomer is composed of 25kg of modified epoxy acrylate resin, 10kg of difunctional polyester acrylate, and 10kg of silicon-modified polyurethane acrylate. The viscosity of the modified epoxy acrylate resin at 25°C is 8000cps, the solid content is ≥98%, and the functionality is 3. The viscosity of the difunctional polyester acrylate resin at 25°C is 8000cps, the solid content is ≥98%, and the functionality is 2. The viscosity of the silicon-modified polyurethane acrylate resin at 25°C is 8000cps, the solid content is ≥98%, and the functionality is 2. cps, solid content ≥98%; free radical curing monomer is composed of 30kg tripropylene glycol diacrylate, 3kg pentaerythritol triacrylate, and 6kg cyclotrimethylolpropane formal acrylate; free radical initiator is composed of 2kg 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2kg ethyl 2,4,6-trimethylbenzoylphenylphosphonate; adhesion promoter is chlorinated polyester resin, and the viscosity of chlorinated polyester resin is 1800cps at 60℃; leveling agent is BYK-361; defoamer is silicone acrylate; wax powder lubricant is PTFE modified polyethylene wax, and PTFE modified polyethylene wax is PEW-0674F, with a particle size of 5um and a drop melting point of 116℃; The preparation method is as follows: S1. Mix 1 kg wax powder lubricant with 4 kg free radical curing monomer, the mass ratio of wax powder lubricant to free radical curing monomer is 1:4, stir, dilute and disperse, add to a sand mill and sand grind for 90 min at a speed of 1000 r / min to obtain wax slurry; the fineness of the wax slurry reaches less than 12.5 um; S2, mixing the free radical curing oligomer, the remaining free radical curing monomer, and the adhesion promoter, stirring at 1200 rpm for 30 min, and mixing evenly to obtain a primary mixture; S3, adding a free radical initiator to the initial mixture, and continuing to mix and stir for 30 minutes to obtain a composite material; S4. Add wax slurry, leveling agent and defoaming agent to the composite material, continue mixing and stirring for 30 minutes to obtain the finished tinplate varnish.
[0032] Embodiment 2: This embodiment differs from Embodiment 1 in that: 44kg of free radical curing oligomer, 39kg of free radical curing monomer, 4kg of free radical initiator, 10kg of adhesion promoter, 0.5kg of leveling agent, 0.5kg of defoaming agent and 2kg of wax powder lubricant; the free radical curing oligomer is composed of 28kg of modified epoxy acrylate resin, 10kg of difunctional polyester acrylate and 6kg of silicon modified polyurethane acrylate, the viscosity of the modified epoxy acrylate resin at 25°C is 8000cps, the solid content is ≥98% and the functionality is 3, the viscosity of the difunctional polyester acrylate resin at 25°C is 8000cps, the solid content is ≥98% and the functionality is 2, the silicon modified polyurethane acrylate resin 2 The viscosity is 8000cps at 5℃, and the solid content is ≥98%; the free radical curing monomer is composed of 30kg of tripropylene glycol diacrylate, 3kg of pentaerythritol triacrylate, and 6kg of cyclotrimethylolpropane formal acrylate; the free radical initiator is composed of 2kg of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2kg of ethyl 2,4,6-trimethylbenzoylphenylphosphonate; the adhesion promoter is chlorinated polyester resin, and the viscosity of chlorinated polyester resin at 60℃ is 1800cps; the leveling agent is BYK-361; the defoaming agent is silicone acrylate; the wax powder lubricant is PTFE modified polyethylene wax, with a particle size of 5um and a drop melting point of 116℃; The preparation method is as follows: S1, 2kg wax powder lubricant and 8kg free radical curing monomer were mixed, the mass ratio of wax powder lubricant to free radical curing agent monomer was 1:4, stirred, diluted and dispersed, added to a sand mill and sanded for 90 minutes at a speed of 1000r / min to obtain wax slurry; the fineness of the wax slurry reached less than 12.5um; S2, mixing the free radical curing oligomer, 31 kg of free radical curing monomer and the adhesion promoter, stirring at 1200 rpm for 30 min, mixing evenly, and obtaining a primary mixture; S3, adding a free radical initiator to the initial mixture, and continuing to mix and stir for 30 minutes to obtain a composite material; S4. Add wax slurry, leveling agent and defoaming agent to the composite material, continue mixing and stirring for 30 minutes to obtain the finished tinplate varnish.
[0033] Embodiment 3: This embodiment differs from Embodiment 1 in that: 65kg of free radical curing oligomer, 27.45kg of free radical curing monomer, 4kg of free radical initiator, 3kg of adhesion promoter, 0.05kg of leveling agent, 0.05kg of defoaming agent, and 0.5kg of wax powder lubricant; the free radical curing oligomer is composed of 35kg of modified epoxy acrylate resin, 15kg of 2-functional polyester acrylate, and 15kg of silicon-modified polyurethane acrylate. The viscosity of the modified epoxy acrylate resin at 25°C is 8000cps, the solid content is ≥98%, and the functionality is 3. The viscosity of the 2-functional polyester acrylate resin at 25°C is 8000cps, the solid content is ≥98%, and the functionality is 2. The silicon-modified polyurethane acrylate resin The viscosity of the resin is 8000cps at 25℃, and the solid content is ≥98%; the free radical curing monomer is composed of 18kg of tripropylene glycol diacrylate, 4kg of pentaerythritol triacrylate, and 5.45kg of cyclotrimethylolpropane formal acrylate; the free radical initiator is composed of 2kg of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2kg of ethyl 2,4,6-trimethylbenzoylphenylphosphonate; the adhesion promoter is chlorinated polyester resin, and the viscosity of chlorinated polyester resin is 1800cps at 60℃; the leveling agent is BYK-361; the defoamer is silicone acrylate; the wax powder lubricant is PTFE modified polyethylene wax, with a particle size of 5um and a drop melting point of 116℃; The preparation method is as follows: S1, 1kg wax powder lubricant and 3.5kg free radical curing monomer were mixed, the mass ratio of wax powder lubricant to free radical curing agent monomer was 1:3.5, stirred, diluted and dispersed, added to a sand mill and sanded for 85min at a speed of 900r / min to obtain wax slurry; the fineness of the wax slurry reached less than 12.5um; S2, mixing the free radical curing oligomer, the remaining free radical curing monomer, and the adhesion promoter, stirring at 1000 rpm for 35 min, and mixing evenly to obtain a primary mixture; S3, adding a free radical initiator to the initial mixture, and continuing to mix and stir for 35 minutes to obtain a composite material; S4. Add wax slurry, leveling agent and defoamer to the composite material, continue mixing and stirring for 35 minutes to obtain the finished tinplate varnish.
[0034] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: 45kg of free radical curing oligomer, 39kg of free radical curing monomer, 4kg of free radical initiator, 10kg of adhesion promoter, 0.5kg of leveling agent, 0.5kg of defoaming agent and 1kg of wax powder lubricant; the free radical curing oligomer is composed of 25kg of modified epoxy acrylate resin, 10kg of difunctional polyester acrylate and 10kg of silicon modified polyurethane acrylate; the free radical curing monomer is composed of 30kg of tripropylene glycol diacrylate, 3kg of pentaerythritol triacrylate and 6kg of cyclotrimethylolpropane formal acrylate; the free radical initiator is composed of 2kg of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2kg of ethyl 2,4,6-trimethylbenzoylphenylphosphonate; the adhesion promoter is chlorinated polyester resin with a viscosity of 1800cps at 60°C; the leveling agent is BYK-361; the defoaming agent is silicone acrylate; the wax powder lubricant is wax powder PEW-0724.
[0035] Comparative Example 2: The difference between this comparative example and Example 1 is that: 45kg of free radical curing oligomer, 39kg of free radical curing monomer, 4kg of free radical initiator, 10kg of adhesion promoter, 0.5kg of leveling agent, 0.5kg of defoaming agent and 1kg of wax powder lubricant; the free radical curing oligomer is composed of 35kg of modified epoxy acrylate resin and 10kg of difunctional polyester acrylate; the free radical curing monomer is composed of 30kg of tripropylene glycol diacrylate, 3kg of pentaerythritol triacrylate and 6kg of cyclotrimethylolpropane formal acrylate; the free radical initiator is composed of 2kg of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2kg of ethyl 2,4,6-trimethylbenzoylphenylphosphonate; the adhesion promoter is chlorinated polyester resin with a viscosity of 1800cps at 60°C; the leveling agent is BYK-361; the defoaming agent is silicone acrylate; the wax powder lubricant is wax powder PEW-0647F.
[0036] Comparative Example 3: The difference between this comparative example and Example 1 is that: 45kg of free radical curing oligomer, 39kg of free radical curing monomer, 4kg of free radical initiator, 10kg of adhesion promoter, 0.5kg of leveling agent, 0.5kg of defoaming agent, 1kg of wax powder lubricant; free radical curing oligomer is composed of 25kg of modified epoxy acrylate resin, 10kg of difunctional polyester acrylate, and 10kg of silicon modified polyurethane acrylate; free radical curing monomer is composed of 30kg of tripropylene glycol diacrylate, 30kg of pentaerythritol triacrylate, 30kg of propylene glycol di ... The mixture is composed of 3kg of ester and 6kg of cyclotrimethylolpropane formal acrylic acid; the free radical initiator is composed of 2kg of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2kg of ethyl 2,4,6-trimethylbenzoylphenylphosphonate; the adhesion promoter is chlorinated polyester resin, and the viscosity of the chlorinated polyester resin is 1800cps at 60°C; the leveling agent is BYK-361; the defoaming agent is TEGOAirex920; and the wax powder lubricant is wax powder PEW-0724.
[0037] Performance testing 1. Hardness test The tinplate varnish prepared in Examples 1-3 and Comparative Examples 1-3 was roller-coated on the tinplate coated with the primer (ink & white tin) with a thickness of 6 μm. The varnish of Examples and Comparative Examples was sprayed at 200 mJ / m 2 The energy was used for light curing in a crawler-type mercury lamp curing machine. The paint film pencil method was used for testing with reference to GB / T6739-2006. The hardness of the film layer formed by the tinplate varnish was tested and the data was recorded. At the same time, a commercially available solvent-based varnish (the solvent-based varnish was purchased from Foshan Rulin Chemical Co., Ltd., model BS-UV-3312C) was thermally cured at 180°C for 30 minutes as a control. After curing, the hardness was tested and the data was recorded.
[0038] 2. Adhesion test The tinplate varnish prepared in Examples 1-3 and Comparative Examples 1-3 was roller-coated on the tinplate coated with the primer (ink & white tin) with a thickness of 6 μm. The varnish of Examples and Comparative Examples was sprayed at 200 mJ / m 2 The paint film was subjected to a cross-cut test with reference to GB / T9286-2021, and the adhesion of the film layer formed by the tinplate varnish was tested, and the data was recorded. At the same time, a commercially available solvent-based varnish (the solvent-based varnish was purchased from Foshan Rulin Chemical Co., Ltd., model BS-UV-3312C) was thermally cured at 180°C for 30 minutes as a control. After curing, the adhesion was tested and the data was recorded.
[0039] 3. Anti-scratch test The tinplate varnish prepared in Examples 1-3 and Comparative Examples 1-3 was roller-coated on the tinplate coated with the primer (ink & white tin) with a thickness of 6 μm. The varnish of Examples and Comparative Examples was sprayed at 200 mJ / m2 The film layer formed by the tinplate varnish was tested for scratch resistance by using QGZ paint film scratch tester with reference to GB / T9279-2007, and the data were recorded. At the same time, commercially available solvent-based varnish (the solvent-based varnish was purchased from Foshan Rulin Chemical Co., Ltd., model BS-UV-3312C) was thermally cured at 180°C for 30 minutes as a control, and the scratch resistance test was carried out after curing, and the data was recorded.
[0040] 4. Wear resistance test The tinplate varnish prepared in Examples 1-3 and Comparative Examples 1-3 was roller-coated on the tinplate coated with the primer (ink & white tin) with a thickness of 6 μm. The varnish of Examples and Comparative Examples was sprayed at 200 mJ / m 2 The energy was used for light curing in a crawler-type mercury lamp curing machine, and the dynamic friction coefficient of the film layer formed by the tinplate varnish was tested with reference to ASTM D2534-88 (2017). The instrument was ALTEX 9505 sliding coefficient friction meter to record the data. At the same time, a commercially available solvent-based varnish (the solvent-based varnish was purchased from Foshan Rulin Chemical Co., Ltd., model BS-UV-3312C) was thermally cured at 180°C for 30 minutes as a control. After curing, the dynamic friction coefficient was tested and the data was recorded.
[0041] 5. Impact detection The tinplate varnish prepared in Examples 1-3 and Comparative Examples 1-3 was roller-coated on the tinplate coated with the primer (ink & white tin) with a thickness of 6 μm. The varnish of Examples and Comparative Examples was sprayed at 200 mJ / m 2 The energy is used for light curing in a crawler mercury lamp curing machine, referring to ASTMD2794-93. During the test, an impact steel ball (20mm in diameter, 1kg×2) is raised to a height of 50cm, and then a heavy hammer is allowed to fall freely from a specified height. The punch hits the sample to form a pit. The coating on the protruding part is checked visually or with a specified magnifying glass to see if there is any cracking. The impact resistance of the tinplate varnish is tested and the data is recorded. At the same time, a commercially available solvent-based varnish (the solvent-based varnish was purchased from Foshan Rulin Chemical Co., Ltd., model BS-UV-3312C) is thermally cured at 180℃ for 30min as a control. After curing, a 50cm drop ball impact test is performed and the data is recorded.
[0042] 6. Bending detection The tinplate varnish prepared in Examples 1-3 and Comparative Examples 1-3 was roller-coated on the tinplate coated with the primer (ink & white tin) with a thickness of 6 μm. The varnish of Examples and Comparative Examples was sprayed at 200 mJ / m 2The energy was used for light curing in a crawler-type mercury lamp curing machine, and the film layer formed by the tinplate varnish was subjected to T-bend test with reference to GB / T30791-2014, and the data was recorded. At the same time, a commercially available solvent-based varnish (the solvent-based varnish was purchased from Foshan Rulin Chemical Co., Ltd., model BS-UV-3312C) was thermally cured at 180°C for 30 minutes as a control, and a T-bend test was performed after curing, and the data was recorded.
[0043] In each of the above test items, except that the tinplate varnish samples prepared in the embodiments and comparative examples are different, the other test conditions are the same, which conforms to the single variable method.
[0044] Table 1 Performance test table Combining Examples 1-3 and Comparative Examples 1-3 and the control group and Table 1, it can be seen that the combination of silicon-modified polyurethane acrylate resin, silicone acrylate TEGO2700 defoamer, and PTFE-modified polyethylene wax in the raw materials of tinplate varnish has a great influence on the wear resistance and smoothness of tinplate varnish. The addition of silicon-modified polyurethane acrylate resin improves the long-lasting wear resistance and smoothness of the overall coating by introducing silicon groups into the resin. The TEGO2700 defoamer contains photocurable double bonds, which promotes the rapid floating of small molecule silicon. While defoaming, it can significantly improve the smoothness of the film surface and improve the scratch resistance of the film surface. Its radiation cross-linking properties ensure the long-term stability of the coating smoothness. Compared with ordinary polyethylene wax, PTFE modified polyethylene wax PEW-0674F introduces PTFE groups and utilizes the unique low surface tension characteristics of fluorine to help further reduce the friction coefficient of the coating surface. The lubricant with low surface tension can also reduce the adhesion of dust and stains, thereby improving the pollution resistance of the coating; so that the iron printing varnish can form a strong and smooth surface protective film while having good lubricity, thus having higher wear resistance.
[0045] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A highly wear-resistant UV curing tinplate varnish, characterized in that: The tinplate varnish comprises the following raw materials in percentage by weight: 40-65% free radical curing oligomer, 25-44% free radical curing monomer, 2-4% free radical initiator, 3-10% adhesion promoter, 0.05-0.5% leveling agent, 0.05-0.5% defoaming agent and 0.5-2% wax powder lubricant.
2. The highly wear-resistant UV curing tinplate varnish according to claim 1, characterized in that: The free radical curing oligomer comprises the following raw materials in percentage by weight: 20-30% of modified epoxy acrylate resin, 10-20 parts of difunctional polyester acrylate, and 10-15% of silicon-modified polyurethane acrylate.
3. The highly wear-resistant UV curing tinplate varnish according to claim 1, characterized in that: The free radical curing monomer comprises the following raw materials in percentage by weight: 20-30% of tripropylene glycol diacrylate, 2-4% of pentaerythritol triacrylate, and 3-10% of cyclotrimethylolpropane formal acrylate.
4. The highly wear-resistant UV curing tinplate varnish according to claim 1, characterized in that: The free radical initiator comprises the following raw materials in weight percentage: 2-Hydroxy-2-methyl-1-phenyl-1-propanone 1-2%, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester 1-2%.
5. The highly wear-resistant UV curing tinplate varnish according to claim 1, characterized in that: The adhesion promoter is a chlorinated polyester resin.
6. The highly wear-resistant UV curing tinplate varnish according to claim 1, characterized in that: The leveling agent is BYK-361N.
7. The highly wear-resistant UV curing tinplate varnish according to claim 1, characterized in that: The defoamer is silicone acrylate.
8. The highly wear-resistant UV curing tinplate varnish according to claim 1, characterized in that: The wax powder lubricant is PTFE modified polyethylene wax.
9. A highly wear-resistant UV curing tinplate varnish according to claim 8, characterized in that: The average particle size of the PTFE modified polyethylene wax is 4-6 μm, and the drop melting point is 115-118° C.
10. The method for preparing a highly wear-resistant UV-curable tinplate varnish according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing wax powder lubricant and part of free radical curing monomer, the mass ratio of wax powder lubricant to free radical curing agent monomer is 1:3.5-4.5, stirring, diluting and dispersing, adding to a sand mill and sand milling for 85-95 minutes at a speed of 900-1100r / min to obtain wax slurry; S2, mixing the free radical curing oligomer, the remaining free radical curing monomer, and the adhesion promoter, stirring at 1000-1500 rpm for 25-35 min, mixing evenly, and obtaining a primary mixture; S3, adding a free radical initiator to the initial mixture, mixing and stirring for 25-35 minutes to obtain a composite material; S4. Add wax slurry, leveling agent and defoamer to the composite material, continue mixing and stirring for 25-35 minutes to obtain the finished tinplate varnish.
Citation Information
Patent Citations
Photo-curing silk screen pearly-luster ink applicable to different printing substrates and preparation method thereof
CN102634251A
Varnish for tin plate ink
CN106833362A
UV nano metallic coating material
CN108192495A
UV-LED (Ultraviolet-Light Emitting Diode) curing coating as well as preparation method and use method thereof
CN112226153A
High-hardness wear-resistant UV curing coating
CN116694200A